2015
DOI: 10.1111/1365-2664.12573
|View full text |Cite
|
Sign up to set email alerts
|

Improving spatial arrangement of honeybee colonies to avoid pollination shortfall and depressed fruit set

Abstract: 1. Pollination shortfalls affect yield of many crops, and the use of managed honeybee colonies is a common practice for addressing the problem. However, colony density and arrangement strategies are not generally based on replicated scientific trials, so there is considerable uncertainty regarding effectiveness of different practices. We address this problem with experiments in almond orchards in south-east Australia, considering impacts on honeybee pollen foraging and fruit set. 2. We examined the effect of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…However, macadamia flowers are bee-pollinated [36,38,[40][41][42][43]45,98] and we have demonstrated that nut production is almost totally reliant on the transfer of pollen from one cultivar to another. Therefore, there is the potential for yield to decline with increasing distance from bee hives [104][105][106] or with increasing distance from another cultivar, as found previously in a 27-row block of "A16" trees [40,47].…”
Section: Paternitymentioning
confidence: 67%
“…However, macadamia flowers are bee-pollinated [36,38,[40][41][42][43]45,98] and we have demonstrated that nut production is almost totally reliant on the transfer of pollen from one cultivar to another. Therefore, there is the potential for yield to decline with increasing distance from bee hives [104][105][106] or with increasing distance from another cultivar, as found previously in a 27-row block of "A16" trees [40,47].…”
Section: Paternitymentioning
confidence: 67%
“…This translates into important fluxes of pollinators into agricultural and adjacent seminatural habitats during the flowering season of crops (Box 3). Globally, these managed pollinator species represent around 20 species among all social and solitary bee species (Stout and Morales, 2009 A. mellifera is used for honey production and to pollinate MFC such as almonds (Cunningham et al, 2016), mango (Geslin et al, 2016c), apples (Ramírez and Davenport, 2013), pears (Stern et al, 2004) and many others (Garibaldi et al, 2013(Garibaldi et al, , 2016. Contrary to other Apis species that are restricted to Asia, a the native geographical range of A. mellifera spans from Scandinavia to Central Asia and the African continent (Ruttner, 1988;Seeley, 1985;Sheppard and Meixner, 2003).…”
Section: Box 6 Emergent Mims-megachilementioning
confidence: 99%
“…To compensate for the losses of wild pollinators, or lack thereof in intensively managed farmland areas, modern agricultural practices usually rely on massively introduced managed pollinators (mainly Apis mellifera and Bombus spp.) that sometimes become the unique pollinating species of the targeted crops (Cunningham et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For honey bees, we did not detect any increase in their visitation rate with honey bee colony density within 1000 meter buffers. Honey bee foraging range seems to be highly context dependent, from several hundred meters to several kilometers [44,45]. Additionally, Couvillon et al 2015 demonstrated that honey bee foraging distances both depend on the type of rewards that honey bees seek (nectar or pollen) and on the month considered [46].…”
Section: Discussionmentioning
confidence: 99%